2012
DOI: 10.1103/physrevlett.109.010601
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Adiabatic Transport In Momentum Space

Abstract: Though topological aspects of energy bands are known to play a key role in quantum transport in solid-state systems, the implications of Floquet band topology for transport in momentum space (i.e., acceleration) have not been explored so far. Using a ratchet accelerator model inspired by existing cold-atom experiments, here we characterize a class of extended Floquet bands of one-dimensional driven quantum systems by Chern numbers, reveal topological phase transitions therein, and theoretically predict the qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
152
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(155 citation statements)
references
References 38 publications
1
152
0
Order By: Relevance
“…It has also inspired numerous proposals and experiments for realizing topologically non-trivial bands using light, 4 sound, 5,6 and other types of waves. 7 According to the topological bulk-edge correspondence principle, 8 topologically nontrivial bandstructures imply the existence of topologically-protected edge states, whose unique transport properties may have applications in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…It has also inspired numerous proposals and experiments for realizing topologically non-trivial bands using light, 4 sound, 5,6 and other types of waves. 7 According to the topological bulk-edge correspondence principle, 8 topologically nontrivial bandstructures imply the existence of topologically-protected edge states, whose unique transport properties may have applications in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…One proposal to attain a controllable topological phase is to introduce a driving field (time periodic term) into a system. By using Floquet theory [23][24][25][26], it can be shown that such a driving field can modify the topology of the system's band structure. This method has been used to generate several topological phases such as Floquet topological insulators [27,28] and Floquet Weyl semimetals [29].…”
Section: Introductionmentioning
confidence: 99%
“…Topological invariants have gained considerable interest in solid state physics and related fields through their application to the quantum Hall effect [1,2], topological insulators [3][4][5][6], and more recently, Floquet-Bloch systems [7][8][9][10][11][12][13][14][15][16][17][18][19]. While the relevant topological invariants for the quantum Hall effect are the Chern numbers of the respective bands of the Hamiltonian, the invariants for Floquet-Bloch systems are constructed for unitary maps that are derived from the time propagator of the periodically driven system.…”
Section: Introductionmentioning
confidence: 99%